E-Rupee: The Digital Currency Evolution in India - Deepika Saxena, Nihanshi Goyal (European Economic Letters (EEL), 2023)
This research paper dives into the transformational journey of digital currency development in India, notably concentrating on the notion of the "e-rupee." The study investigates how India's financial environment has altered due to technology improvements and shifting consumer behavior. It analyses the function of the e-rupee, envisioned as a digital alternative to the traditional rupee, in transforming financial transactions and redefining economic connections. The study explores the functioning mechanics, prospective advantages, and issues related with the e-rupee. It also compares the e-rupee with other digital payment systems like UPI and analyses its specific characteristics. The research developed a theoretical framework to understand the factors affecting CBDC adoption in India and to understand the CBDC potential towards financial inclusion. By drawing insights from central bank initiatives, industry reports, and international trends, this research contributes to the ongoing discussions on digital currencies and their significance in India's pursuit of a technologically-driven financial future and how this study will benefit the future scholars, academicians, policy makers and society in various ways.